2021
DOI: 10.3389/fncir.2021.788560
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Cartography: Mapping Arealization Using Single-Cell Omics Technology

Abstract: The cerebral cortex derives its cognitive power from a modular network of specialized areas processing a multitude of information. The assembly and organization of these regions is vital for human behavior and perception, as evidenced by the prevalence of area-specific phenotypes that manifest in neurodevelopmental and psychiatric disorders. Generations of scientists have examined the architecture of the human cortex, but efforts to capture the gene networks which drive arealization have been hampered by the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 112 publications
(145 reference statements)
1
1
0
Order By: Relevance
“…By identifying genes that describe subclasses, we found that GABAergic neurons conserve the most subclass features across regions. These results align with recent studies showing that cell-types vary along a continuum across cortical regions and that glutamatergic neurons exhibit greater differences than interneurons (Bhaduri et al, 2021;Nano et al, 2021;Yao et al, 2021a). The distinct clustering of pyramidal cells between ALM and VISp is thought to be accounted for by a frontal to occipital pole gradient in cell-types (Yao et al, 2021a).…”
Section: Discussionsupporting
confidence: 91%
“…By identifying genes that describe subclasses, we found that GABAergic neurons conserve the most subclass features across regions. These results align with recent studies showing that cell-types vary along a continuum across cortical regions and that glutamatergic neurons exhibit greater differences than interneurons (Bhaduri et al, 2021;Nano et al, 2021;Yao et al, 2021a). The distinct clustering of pyramidal cells between ALM and VISp is thought to be accounted for by a frontal to occipital pole gradient in cell-types (Yao et al, 2021a).…”
Section: Discussionsupporting
confidence: 91%
“…3b ). For example, glutamatergic cells showed arealization 32 among cortical areas within each slice and dorsal–ventral separation was observed among medium spiny neurons dissected from the caudoputamen (CP) and nucleus accumbens (ACB) regions. Moreover, many subcortical dissection borders were faithfully preserved in the imputed spatial embedding.…”
Section: Spatial Epigenomic Diversitymentioning
confidence: 99%